159k views
3 votes
Consider the equation:

0 = x^2 - 10x + 10
1) Rewrite the equation by completing the square.
Your equation should look like (x + a)2 = b or (x - c)2 = d.

User OnResolve
by
5.3k points

2 Answers

11 votes
x² - 10x + 10 = 0

Isolate the constant term

x² - 10x = -10

Complete the square
• coefficient of the x term: -10
• divide in half: -5
• square it: (-5)² = 5²
• add 5² to both sides, to complete the square and keep the equation balanced:
x² - 10x + 5² = -10 + 5²
(x-5)² = 15
User Layser
by
5.6k points
10 votes

Answer:

1) We can rewrite the equation as 15=(x-5)^2

2) The solutions to the equation are x=5±15

User Timidfriendly
by
5.5k points